Self-Disclosure Patterns Among Children and Youth with Epilepsy: Impact of Perceived-Stigma - Clifford LM; Brothers SL; Lang A (Dove Medical Press, 2023)
Lisa M Clifford, Shannon L Brothers, Amy Lang Division of Behavioral Medicine and Clinical Psychology, Cincinnati Children's Hospital Medical Center, Cincinnati, OH, USACorrespondence: Lisa M Clifford, Division of Behavioral Medicine and Clinical Psychology, Cincinnati Children's Hospital Medical Center, 3333 Burnet Ave, MLC 3015, Cincinnati, OH, 45229, USA, Tel +1 513 803 3409, Fax +1 513 636 7756, Email Lisa.clifford@cchmc.orgAbstract: This review aimed to synthesize the minimal existing literature on the impact of perceived stigma on self-disclosure patterns among children and youth with epilepsy (YWE). Initial literature searches were conducted in PsycInfo, Scopus, Web of Science, and PubMed using search terms focused on epilepsy, pediatrics, disclosure, and/or stigma. Articles were included if they were original human research articles published in peer-reviewed journals that were accessible in English through Cincinnati Children's Hospital Medical Center Pratt Library and fit study aims. Thirteen articles, which primarily used qualitative self-report methodologies, fit the study's inclusion criteria. YWE report greater perceived stigma and lower illness disclosure compared to youth with other chronic health conditions. Across studies, perceived stigma was consistently identified as a barrier to YWE disclosing their epilepsy diagnosis. Consequences of perceived stigma included lower self-esteem, poorer perceived competency, lack of self-confidence, social withdrawal, and lower quality of life. YWE's reluctance to disclose epilepsy was associated with worry about differential treatment, negative impact on close relationships, negative impact on others' perceptions, and negative self-perceptions. While WHO and ILAE have identified stigma as contributing to higher disease burden in people with epilepsy and have highlighted the importance of prioritizing social policy focused on decreasing epilepsy-related stigma, progress has been incremental and much work remains. Future research is needed to understand socio-cultural factors perpetuating stigma among YWE in order to further develop, evaluate, and disseminate evidence-based clinical and education programming to combat epilepsy-related stigma.Keywords: attitudes, enacted stigma, secrecy, adolescent, children, parents